Molecular Fingerprinting of Heavy Metal-resistant Bacteria through FTIR Analysis Under Heavy Metal Stress - Ritika Garg; Shweta Dang; Pammi Gauba (Journal of Pure and Applied Microbiology)
Heavy metal contamination of soil and water poses serious risks to human health and ecosystems. This study focuses on two bacterial strains, Achromobacter insolitus PGRG5 and Enterobacter sp. PGRG2, known for their tolerance and bioaccumulation of lead (Pb), cadmium (Cd), and nickel (Ni). Their potential for bioremediation was examined using Fourier-transform infrared (FTIR) spectroscopy. The bacteria were cultured in nutrient broth containing heavy metals (1000 ppm Pb(NO3)2, 750 ppm CdCl2‚ ·H2O, 200 ppm Ni (NO3 )2 ) to assess changes in biomolecular structures due to metal exposure. FTIR analysis revealed distinct and specific binding interactions between heavy metal ions and bacterial functional groups. These interactions include hydrogen bonding with hydroxyl (O-H) and amine (N-H) groups, ionic interactions with negatively charged phosphate and carboxyl groups, and coordination bonds with carbonyl (C=O) and amino groups in proteins. The evidence for these mechanisms was observed through shifts in key FTIR peaks, such as the O-H and N-H stretching regions (e.g., 3280.1 cm-1), phosphate stretching vibrations (e.g., 1233.7 cm-1), and amide I and II peaks (e.g., 1636.3 cm-1 and 1528.2 cm-1). These interactions provide insights into the mechanisms of metal bioaccumulation and stress adaptation. The findings highlight Enterobacter sp. PGRG2 and Achromobacter insolitus PGRG5 as promising candidates for bioremediation, offering potential solutions for mitigating heavy metal pollution in contaminated environments.